Research Into improved Distance Learning Using VR Technology - Li, Pengfei; Fang, Zelong; Jiang, Tan (Frontiers in Education, 2022)
Practical skill-based education requires exemplary face-to-face operational teaching, and VR can enhance online distance learning, facilitating an alternative form of “face-to-face” teaching, which results in better teacher–student communication and learner self-efficacy. It also constitutes as a useful substitute for in-person teaching, and it also has a positive impact on learning effectiveness. In this study, a mixed-method approach was used, which utilized the following methodologies: a combination of quantitative and qualitative measures, document collection, case and comparative analysis, and VR teaching that utilizes “You, Calligrapher” as a survey tool. Teachers and students of art were selected, who then used an educational VR-based calligraphy game application for teaching activities. We investigated the impact of virtual time, space, and technical availability on learners’ understanding, imagination, and interactivity in VR education, and then we evaluated the positive impact via learner feedback. Research tools that we utilized consist of comprehension, imagination, and how feedback motivation scales with effective learning; we have also used Chinese calligraphy performance tests. The SPSS statistical analysis software was used for related statistical processing, and α was set to 0.05. The results of this study indicated that Chinese calligraphy studies in VR time and space affect students’ understanding and imagination but not their operational abilities. According to our research, a fundamental difference between traditional and modern teaching methods is a shift toward the use of VR (and the internet) in education. Therefore, the focus of this study is on understanding the impact on practical skills during distance learning and investing the impacts in order to form an effective approach to the use of VR in education.